Diet of labuanium politum (an obligate arboreal crab) at Kampung Tanjong Assam, Spaoh, Sarawak - Nur Amirah, binti Mohamad Alwie (Universiti Malaysia Sarawak (UNIMAS), 2016)
Labuanium politum is an obligate arboreal crab that belonged to Family Sesarmidae and can be found at nipah palm mangrove in Kampung Tanjong Assam, Spaoh, Sarawak. It is known as `Geramak apong' by local people. It lives and hides inside the base fronds of the nipah tree. On 7-9 November 2015,68 samples for diet composition and comparison of the stomach fullness of these crabs at disturbed and undisturbed nipah palm area were obtained using special hooks `pengait'. Later, the second samplings were done on 23`d March 2016 for the observation of the feeding behavior of this crab where three samples were obtained. Results showed that this crabs highly preferred debris (100%) and plant materials (80%) as their primary consumption on disturbed nipah palm area compared to undisturbed area where only 57.5% and 70% of debris and plant materials, respectively. For the overall of the stomach fullness of crabs, higher stomach fullness were observed during night time (41.7%) compared to day time (23.2%). Comparing the crabs that were caught at night time, disturbed area showed higher stomach fullness (75%) than the undisturbed area (25%). For the feeding behavior experiment, it is proven that this crab is nocturnal. L. politum strongly preferred green leaves of Nypa fruticans when offered three different types of categories of the leaves (green, yellow, brown). Therefore, this study provides a new information on the diet of L. politum as this is a first attempt to record diet of this crabs.